Implementation of the ATmega 328 microcontroller in the Room Light Control System - rizky ramdhani (Institut Pendidikan Indonesia, 2020)
This research is an effort to save on the use of electrical energy at home, by designing and building an automatic room light control system using a PC and an ATmega 328 microcontroller which is used as a module on the Arduino uno. The research method used is a quasi-experimental method by calculating the average time consumption required when using a control system. From the results of the analysis carried out, it was concluded that for each procedure used in the test it produced a very good average response time because it was not more than 1 second and did not cause a long delay in the execution of control commands.